ANALYSIS OF DIESEL OPERATIONAL PROCESS WHILE USING BIO-FUEL - O. A. Ivashkevich; G. M. Kuharenok; A. N. Petruchenko; Yu. V. Grigoriev; A. A. Zelenkov (Наука и техника)
A model for diesel operational process has been developed and this model takes into account composition and physical and chemical properties of mixed fuels. Operational processes of 4ЧН 11/12.5 have been analyzed and this analysis makes it possible to evaluate influence of physical and chemical properties of bio-fuels on combustion process, ecological and economic indices of their operation.